Preliminary critique of Sikolohiyang Pilipino - San Juan, Epifanio, Jr. (Miag-ao UP Visayas, 2005)
"Sikolohiyang Pilipino (SP) is a project of filipino intellectuals to invent a discipline of psychological research and analysis of Filipino everyday life and personality based on indigenous filipino culture. The emergence of SP coincided with the intensification of ethnic and national in the Philippines during the period of the Marcos dictatorship, the rise of Muslim separatism, and the salience of indigenous communities in the political science. However, its reliance on questionable linguistic assumptions and unmediated logical inferences leaves SP open to critical refutation. In particular, SP's tendency to fetishize certain notions not grounded in a consistent theory of the psyche compels it to downplay individual experience in favor of an unmediated emphasis on a presumed and largely untheorized notion of "a people with a common bond of history." This ignores the class and other structural antagonism that distinguish the nationalist struggle. In particular, SP ignores the concrete dialectic between the life-itinerary of the individual and the totality of social relations that historically define individual and collective psychological behavior and processes. What is needed is a clear identification of the role of culture and language in relation to political economy operating in the historical formation of the Filipino national identity."
Keywords: Psychology -- Philippine